Adults and children prefer a plate food guide relative to a pyramid - Talati, Zenobia; Pettigrew, S.; Moore, S.; Pratt, I. (2015)
Background and Objective: This study explored attitudes toward two food guides currently being widely used in Australia: the Healthy Eating Pyramid and the Australian Guide to Healthy Eating Plate. Methods and Study Design: Ten focus groups were conducted with adults (aged 18+ years) and children (aged 10-17 years) across various locations in Perth, Western Australia. The discussions focused on liked and disliked aspects of each food guide and the implications for participants' perceptions of their relative usefulness. Results: When asked to state their preference, a large majority of participants nominated the plate as their preferred nutrition guide. The style of presentation used for the plate was reportedly clearer and more aesthetically pleasing. The plate was also perceived to be more complex while the pyramid was considered by adults to be more child-friendly. Conclusions: This study provides information on consumers' reactions to different food guides and the implications for perceived relevance and utility.